2022
DOI: 10.1111/jocs.17027
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical characteristics of different methods of neo‐chordal fixation to the papillary muscles

Abstract: Background and Aim of the Study: Several techniques have been described for neochordal fixation to the papillary muscles without any reported clinical differences.The objective of this study is to compare in vitro the biomechanical properties of four of these common techniques. Methods:We studied the biomechanical properties of expanded polytetrafluoroethylene neo-chordal fixation using four techniques: nonknotted simple stitch, nonknotted figure-of-eight stitch, knotted pledgeted mattress stitch, and knotted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…However, all the suture pull-out forces observed in their experiments vastly exceeded the forces usually observed for the primary or secondary chordae tendineae [159]. A recent study by Fernández and colleagues showed that different techniques of anchoring the neochords at the papillary muscles may influence neochordal biomechanics; however, this is not the case when reviewing the loading conditions within the physiological range [160]. Classically, neochords are affixed to the papillary muscle tips, restoring more normal mechanics; however, recent biomechanical evidence suggests that alternative implantation into the apical or posterior myocardium may provide satisfactory mitral valve repair, as well [38,146,161].…”
Section: Surgical Repair Techniquesmentioning
confidence: 89%
“…However, all the suture pull-out forces observed in their experiments vastly exceeded the forces usually observed for the primary or secondary chordae tendineae [159]. A recent study by Fernández and colleagues showed that different techniques of anchoring the neochords at the papillary muscles may influence neochordal biomechanics; however, this is not the case when reviewing the loading conditions within the physiological range [160]. Classically, neochords are affixed to the papillary muscle tips, restoring more normal mechanics; however, recent biomechanical evidence suggests that alternative implantation into the apical or posterior myocardium may provide satisfactory mitral valve repair, as well [38,146,161].…”
Section: Surgical Repair Techniquesmentioning
confidence: 89%
“…Pre-measured neo-chordae (loop technique), also present in the market and ready-to-use, have facilitated and propagated mitral repair by using this technique. 12 In this paper, Fernandez et al, 15 This is an interesting experimental in vitro design study aiming to evaluate and to compare different stitching techniques in use to anchor PTFE neo-chordae to papillary muscles during mitral valve repair. In my opinion, the greatest limitation of this study is its in vitro design.…”
Section: Indead Ptfe Neo-chordae Implantation Has Been In Clinical Usementioning
confidence: 99%
“…In this paper, Fernandez et al,15 Santiago de Compostela, Spain and from Kingston, Canada, present an interesting in vitro study focusing on the first of the technical details of neo-chordae implantation previously mentioned, that is the attachment on the papillary muscle. They compared different stitching techniques in use to anchor neo-chordae to papillary muscles and evaluated the impact of each method on the biomechanical properties of PTFE.…”
mentioning
confidence: 99%